Multiple phases of carbon cycle disturbance from large igneous province formation at the Triassic-Jurassic transition - Ruhl, M; Kürschner, WM (2011)
The end-Triassic mass extinction (ca. 201.4 Ma) coincided with a major carbon cycle perturbation, based on an ~5%‰-6%‰ negative excursion in δ13CTOC (total organic carbon) records. Both events coincided directly with the onset of massive flood basalt volcanism in the Central Atlantic Magmatic Province (CAMP). Organic carbon isotope data from the western Tethys Ocean (Austria) and the Germanic basin (UK and Germany), however, demonstrate earlier disruption of the global carbon cycle, preceding CAMP eruptions. A 2%‰-3%‰ late Rhaetian precursor negative excursion in marine and continental δ13CTOC records is matched by a negative perturbation in δ13Cleaf data, suggesting multiple events of Rhaetian atmospheric 13C depletion. Intruding dike and sill systems, preceding CAMP eruptive volcanic activity, may have released ~3000-7000 Gt of isotopically light carbon as thermogenic methane from subsurface organic-rich strata. This possibly caused an end-Triassic atmospheric pCO2 increase and reduced ecosystem stability before the actual onset of eruptive volcanic activity in the CAMP region. We present a model that identifies three phases of disturbances in global biogeochemical cycles related to the formation of this large igneous province. © 2011 Geological Society of America.